Identification of SNPs and Candidate Genes Associated with Growth Using GWAS and Transcriptome Analysis in Portuguese Oyster (Magallana angulata) - Jingyi Xie; Yue Ning; Yi Han; Caiyuan Su; Xiaoyan Zhou; Qisheng Wu; Xiang Guo; Jianfei Qi; Hui Ge; Yizou Ke; Mingyi Cai (Fishes)
Portuguese oyster (Magallana angulata) is one of the most important shellfish species worldwide. Although significant improvements in growth have been achieved through artificial selection breeding, the genetic basis underlying these traits remains unclear. Thus, this study aimed to (i) estimate variation and heritability for growth-related traits and (ii) identify SNPs and candidate genes associated with growth traits in Portuguese oyster. Five growth-related traits, including shell height (SH), shell length (SL), shell width (SW), whole weight (WW), and soft tissue weight (STW), were measured and analyzed in 114 one-year-old individuals from a cultivated population in Fujian Province, China. Through whole-genome sequencing and genotyping, we obtained 8,183,713 high-quality SNPs. Based on the genomic relationship matrix, heritability for the five traits was estimated, ranging from 0.071 to 0.695. Through genome-wide association analysis (GWAS), a total of nine SNPs were identified as significantly or suggestively associated with one of the growth-related traits, each explaining phenotypic variation ranging from 14.13% to 18.56%. Differentially expressed genes (DEGs) between individuals with extreme phenotypes were identified using comparative transcriptome analysis, ranging from 868 to 2274 for each trait. By combining GWAS and comparative transcriptome analysis, a total of seven candidate genes were identified, with biological functions related to growth inhibition, stress response, cell cycle regulation, and immune defense. The associations between the candidate genes and the growth-related traits were validated by using single-marker association analysis in other populations. Based on SNPs in these candidate genes, 16 haplotypes associated with growth-related traits were obtained. This study contributes to a deeper understanding of the genetic mechanisms of growth traits, and provides a theoretical basis and genetic markers for the breeding of fast-growing strains of the Portuguese oyster.